“It helps me get closer to their writing experience” Classroom ethnography and the role of technology in third-year FL courses - Gleason, Jesse (System, 2014)
Research has shown a disjunction between language instruction at the lower and upper levels of foreign language (FL) study. Whereas lower-division courses focus on grammatical patterns, upper-level courses focus on specific content. The third-year writing course is in a unique position to help learners prepare for the types of learning that they will encounter in more advanced language use contexts. Using grounded classroom ethnography, this multiple case study of two classrooms chronicles how a collaborative partnership between an instructor and an applied linguist facilitated the integration of two types of technology into a third-year Spanish writing course at a North American University. Technology was carefully chosen based on pedagogical considerations and teacher goals. Students in these courses included a mixture of heritage and FL Spanish learners with a mean age of 21 years. Findings included four ways that technology played a role in third-year Spanish language learning, including as: (a) a way to alleviate their workloads, (b) a motivator, (c) a way to improve the quality and quantity of feedback students received in the course, and in some cases (d) antagonistic to language learning. Implications of classroom ethnography for research on blended learning are drawn. Published by Elsevier Ltd.
4 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000345155800012, lens.org/016-859-492-698-057 tex.type: [object Object]
Keywords: Blended language learning; Discourse analysis; Ethnography; Language-content gap; Spanish; Teacher-researcher collaboration; Technology; Third-year FL courses; Writing; dept.wll